Analisis Manajemen Kepemimpinan Melalui Aplikasi Swot Pada Organisasi PSSI (Persatuan Sepakbola Seluruh Indonesia) - veno, andri (Benefit: Jurnal Manajemen dan Bisnis, 2016)
Just like an umbrella, PSSI, official Indonesian football organization have been changing toÂ fulfill several organizational goals, and still undergoing some functions alongside regulation of FIFA andÂ Indonesian law for the glorious and prestigious Indonesian football. In reorganizing PSSI, the governmentÂ under The Ministry of Educations and Sports (Kemenpora) takes over PSSIâs role temporarily to rearrangeÂ management of the organization, and then the problems regarding to mafia and political issues inside ofÂ PSSI management can be resolved immediately. The management changes by the government is expectedÂ to become a turning point for the development of the future PSSI organization, so it can be reciprocal bothÂ with mission and vision of PSSI. The recent step from the government under Kemenpora in order to makeÂ all of the football perpetrators running their job is hold a tournament with competition system.